Dificuldades e limitações na marcação de pontos cefalométricos em cortes tomográficos e reconstruções tridimensionais - Neiva, Marcelo Baião da (2013)
The aim of this study was to evaluate the reliability of landmark identification in cone beam computed tomography (CBCT) images of patients undergoing orthodontic treatment. The sample consisted of 12 scans generated from the iCat - 3D and evaluated through the software InVivoDental 5.1 , where three observers worked independently on the identification of 30 landmarks in three time - points , using two different imaging analyzes: one based on tomographic axial, coronal and sagittal slices , and other on three - dimensional reconstruction. V alues of X, Y and Z coordinates were automatically generated by the software for each point, and intraclass correlation coefficients (ICC) were calculated between the markings. A frequency distribution divided the ICC values above 0.90 (highly reliable ), between 0.75 and 0.90 (reliable), between 0.45 and 0.75 (a cceptable) and below 0.45 ( unreliable ). In the 3D reconstruction images an ICC> 0.90 was achieved in 67.76% and 45.56% of the intraobserver and interobserver assessments, respectively. An ICC ≤ 0,45 was observed in 13,33% and 14,46%, respectively. In the tomographic slices views the ICC was > 0.90 for 82.16% and 78.56% of intraobserver and interobserver evaluations, respectively, while an ICC ≤ 0.45 was observed in only 7.16% and 8.33 %. I n p oints presenting poor reliability , it occu rred mostly in just one plane of space, or at most two, indicating that finding some points is more difficult depending on the structure to be visualized. Overall , an excellent intra and interobserver reliability was observed for both imaging modalities, suggesting that 3D cephalometric measurements would be feasible based on these anatomic landmarks using the tested software.